(3+1)D printed adiabatic 1-to-M broadband couplers and fractal splitter networks - Grabulosa, Adrià; Porte, Xavier; Jung, Erik; Moughames, Johnny; Kadic, Muamer; Brunner, Daniel (Optics express, 2023)
We experimentally demonstrate, based on a generic concept for creating 1-to-M couplers, single-mode 3D optical splitters leveraging adiabatic power transfer towards up to 4 output ports. We use the CMOS compatible additive (3+1)D flash-two-photon polymerization (TPP) printing for fast and scalable fabrication. Optical coupling losses of our splitters are reduced below our measurement sensitivity of 0.06 dB by tailoring the coupling and waveguides geometry, and we demonstrate almost octave-spanning broadband functionality from 520 nm to 980 nm during which losses remain below 2 dB. Finally, based on a fractal, hence self-similar topology of cascaded splitters, we show the efficient scalability of optical interconnects up to 16 single-mode outputs with optical coupling losses of only 1 dB.